Faith-science transdisciplinary study: mitigating disasters in Muslim communities - Shalihin, Rahmat Ryadhush (Practical theology, 2025)
This study responds to the escalating global concerns surrounding disaster management. The primary objective is to investigate the pivotal role played by Muhammadiyah in developing disaster mitigation framework. Employing a transdisciplinary approach within the fiqh of disaster, this study highlights the significance of effective mitigation, bridging religious and scientific knowledge. The framework encompasses risk assessment, hazard possibilities, vulnerabilities, and capacities. Grounded in values such as monotheism, gratitude, and justice, this study serves as a model for tailoring disaster preparedness strategies in Muslim societies. The study underscores the need to integrate scientific and religious viewpoints in diverse and disaster-prone regions.